Pengaruh Semangat Kerja dan Inovasi Kerja Terhadap Kualitas Kerja Pegawai pada Dinas Pendidikan dan Kebudayaan Provinsi Gorontalo - Fikar, Samsul; Ahmad, Muchtar; Tantawi, Reskiawan (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to find out how much influence work enthusiasm and work innovation have on the quality of work of employees at the Gorontalo province education and culture service. The population in this study were employees at the Gorontalo province education and culture service, namely 156 employees. The sampling technique used was random sampling technique. The number of samples in this study was 112 respondents and used the Slovin formula. Data collection uses questionnaires, observation, documentation and interviews. Analysis test tools using multiple linear regression analysis and statistical analysis methods using the SPSS 26 application. The results of this research show that, (1) work morale has a positive and significant effect on employee work quality; (2) work innovation has a positive and significant effect on employee work quality; (3) Simultaneously (together) work enthusiasm and work innovation have a positive and significant effect on work quality. To improve the quality of employee work, agencies need to pay attention to increasing employee morale and work innovation, so that work discipline and responsibility can be implemented that target improvements in solving problems in every job. So that if the work spirit and work innovation of employees at the Gorontalo provincial education and culture service is better, it will have an impact on improving the quality of work in every job they do.